Education in South Africa - Van Der Berg, Servaas; Hofmeyr, Heleen (World Bank, Washington, DC, 2018)
This note provides an overview of South Africa’s education system and learning outcomes. It reviews early childhood development, basic education, and higher education (university education and vocational training). It is a review of available research in support of the South Africa Systematic Country Diagnostic.